Os impactos do PIBID na formação inicial de professores de Língua Portuguesa - Baltor, Cristiane da Silva (2020)
The main objective of this thesis is analyze the impacts of PIBID on the initial training of Portuguese language teachers. To achieve this goal, we adopted the transdisciplinary perspective of Applied Linguistics, focusing on teacher training, which allowed us to overcome disciplinary barriers, establishing a dialogue with the most diverse areas of knowledge, especially with the area of Languages/Linguistics and Education. The participants in this research are Portuguese language teachers from the public basic education, who acted as teaching assistants inteaching of the subproject URCA Letras Português, for at least three years, since the first Public Call URCA/PROGRAD/PIBID Nº. 001/2014. Data were obtained through semi-structured interviews, when the participants had the opportunity to recall their initial training and reflect on their practices. During the reading of the narratives, the categories of analysis emerged, which were structured as follows: a) the beginning of the trajectory; b) ways of teaching; c) beyond grammar; d) ways of becoming a teacher. The basis of the study was to discuss these categories, based on a qualitative approach. Thus, in general, the results showed that PIBID contributed significantly to the personal, academic and professional growth of the participants, which led us to the following conclusion: the subproject URCA Letras Português (2014-2018) provided them with a unique contact with the classroom, preparing them for pedagogical practice in the context of basic education. In addition, it gave the undergraduate students a chance to reflect on the teaching of the Portuguese language.